The Effects of the 2016 Copa América Centenario Victory on Social Trust, Self-Transcendent Aspirations and Evaluated Subjective Well-Being: The Role of Identity With the National Team and Collective Pride in Major Sport Events - Bravo, Diego; Oriol, Xavier; Gómez, Marcos; Cortez, Diego; Unanue, Wenceslao (Frontiers in Psychology, 2020)
Following a neo-Durkheimian perspective, major sporting events such as the World Cup or the America's Cup differ from other collective rituals because they promote interest throughout the nation due to their massiveness and international character. In order to increase the scientific knowledge related to these type of rituals, the aim of this study was to observe the effects that the Chilean victory in the 2016 Copa América Centenario had on social variables such as trust, self-transcendent aspirations and evaluated subjective well-being (SWB) of both fans and non-fans. In addition, two longitudinal SEM models were performed to estimate the effect of identity with the national team before the final match on evaluated SWB, trust, and self-transcendent aspirations post-final. A total of 648 Chilean participants (mean age = 38.58; SD = 10.96) answered the questionnaire before the final match. Out of these, 409 completed our measures after the final. The results show that fans presented higher scores in many of the studied variables before and after the final compared to non-fans. Identification with the national team (before the final) prospectively and significantly predicted pride in the national team and pride in the country (after the final). In addition, these two forms of collective pride mediated the relationship between identification with the national team (before the final) and evaluated SWB (after the final). The results are discussed emphasizing the importance of these kinds of specific massive rituals and their effects.